Achieving and Maintaining Price Stability in Nigeria - Batini, Nicoletta (IMF Working Papers; Working Paper ;, 2004)
This paper reviews the historical performance of monetary policy in Nigeria and discusses the relative merits of alternative monetary policy strategies that Nigeria could adopt in the future, once the many operational issues that today obstruct the conduct of monetary policy have been addressed. An analysis of external and fiscal dominance in Nigeria reveals that none of the candidate strategies is particularly appealing although, on various grounds, a long-run target for inflation combined with a free float seems to be the ultimate option. The paper shows how to design and operationalize such a regime in Nigeria when account is taken for the emerging market features of the economy.